On Orbifold Criteria for Symplectic Toric Quotients - Farsi, C.; Seaton, C.; Herbig, H.-C (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
We introduce the notion of regular symplectomorphism and graded regular symplectomorphism between singular phase spaces. Our main concern is to exhibit examples of unitary torus representations whose symplectic quotients cannot be graded regularly symplectomorphic to the quotient of a symplectic representation of a finite group, while the corresponding GIT quotients are smooth. Additionally, we relate the question of simplicialness of a torus representation to Gaussian elimination.